Integrated Ayurvedic Strategies for Obesity: A Case Report of Multidimensional Care (AYUSHDHARA, 2024)
Worldwide obesity has nearly doubled between 1990 and 2022. In 2022, over 890 million people over 18 years and older were found to be obese. Obesity is a pathological condition characterized by excessive accumulation of body fat leading to detrimental effects on health. In Ayurveda, obesity has been described as Sthoulya or Medoroga in Santarpanjanya Vikara i.e., the disease caused by over nourishment. A single case study of 45 year old female patient with complaints of increased body weight for 5 years. Associated with exertion on minimal work and pain in lumbo-sacral region, both knee joints. Patient had no history of hypertension, diabetes and hypothyroidism. Considering other biochemical and physical examinations with BMI (38.3Kg/m2) patient was diagnosed as Obese Class II. After detailed history taking and thorough examinations patient was planned to intervene with oral medications (Panchatikta Ghreeta-Guggulu, Arogyavardhini Vati, Vidangadi Lauha and Varunadi Kashayam), Udvartan (massage with therapeutic powder), Pathyaahar (therapeutic diet- Vyoshadi Saktu) and Yoga sessions for 10 days. The patient was advised to continue with the same medications, Pathyaahar and Yogasana for 3 months. This integrated treatment approach yielded desired and significant improvement in the condition of the patient. This case demonstrates safe and convenient approach in the management of Obesity as per Ayurveda and paves way for further research.